Sonate (in Es-dur) für das Piano-Forte von L. van Beethoven. 1tes Werk. No. 1 .. - Beethoven, Ludwig van, 1770-1827 (composer)::::::::::::::: (Vienna; Austria; Tobias Haslinger, 2022)
Edition of the Piano Sonata in E-flat major, WoO 47, no. 1, from Series I, no. 1 of the "Sämtliche Werke von Ludw. van Beethoven" published by Tobias Haslinger; lacks title page but includes the dedication leaf to Archduke Rudolph. Includes metronome markings.